Islamic spirituality stress coping mechanisms: some empirical evidences - Zin, Razali Mat (Ifma Publishing, 2022)
The study aims to assess the religious stress coping mechanisms used by selected Muslim students majoring in Bachelor of Business Management (BBM) undergraduate studies at Universiti Islam Sultan Sharif Ali (UNISSA). Data were collected through interview and thematic analysis procedures were utilized for data analysis. The findings showed that majority of the respondents experienced severe level of stress. Some managerial and future research were recommended.